On the autorotation of animal wings. - Ortega-Jimenez, Victor Manuel; Martín-Alcántara, Antonio; Fernández-Feria, Ramón; Dudley, Robert (The Royal Society, 2017)
Botanical samaras spin about their centre of mass and create vertical aerody- namic forces which slow their rate of descent. Descending autorotation of animal wings, however, has never been documented. We report here that isolated wings from Anna’s hummingbirds, and also from 10 species of insects, can stably autorotate and achieve descent speeds and aerodynamic performance comparable to those of samaras. A hummingbird wing loaded at its base with the equivalent of 50% of the bird’s body mass descended only twice as fast as an unloaded wing, and rotated at frequen- cies similar to those of the wings in flapping flight. We found that even entire dead insects could stably autorotate depending on their wing pos- tures. Feather removal trials showed no effect on descent velocity when the secondary feathers were removed from hummingbird wings. By contrast, partial removal of wing primaries substantially improved perform- ance, except when only the outer primary was present. A scaling law for the aerodynamic performance of autorotating wings is well supported if the wing aspect ratio and the relative position of the spinning axis from the wing base are included. Autorotation is a useful and practical method that can be used to explore the aerodynamics of wing design.
https://openpolicyfinder.jisc.ac.uk/id/publication/11598
Keywords: Mecánica de fluidos; Biomecánica; Aerodinámica